TINJAUAN YURIDIS PERJANJIAN PEMBORONGAN PEKERJAAN ANTARA PT ABC DAN PT XYZ - Yuhao, Sun; Indiraharti, Novina Sri (Tribuere, 2023)
Engagement according to Prof. Subekti is a legal relationship between two people or two parties, based on which one party has the right to demand something from another party, and the other party is obliged to fulfill that demand. Apart from that, the terms of the contract itself are regulated in article 1313 of the Civil Code which explains that an agreement is "An agreement is an act in which one or more people bind themselves to one or more other people." In this case, there is a contracting agreement as previously referred to by author, namely the contracting agreement for the construction of the ABC Tower project, the problem with this agreement is whether the contracting agreement agreed and signed by PT ABC has fulfilled the conditions for the validity of the agreement and whether PT ABC's actions in not carrying out its obligations can be categorized as an act of default and what are the consequences of the status the default. The research in this scientific work uses descriptive characteristics to provide an overview of whether or not the contracting agreement agreed and signed by PT ABC is appropriate and how the legal consequences and categories of an act can be considered an act of default. Referring to Article 1320 of the Civil Code, for an agreement to be valid, four conditions are required, their agreement to bind them; the ability to make an agreement; a certain thing; a lawful cause. If the creditor party in the agreement defaults, it will have consequences that can used or pursued by the debtor, namely Fulfillment of the agreement; Fulfillment of the agreement accompanied by compensation; Just compensate; Cancellation of agreement; Cancellation of the agreement is accompanied by compensation.